GAYA KOMUNIKASI KESEHATAN APOTEKER DI MEDIA SOSIAL : Analisis Semiotika Roland Barthes Pada Akun Instagram @apoteker_rahmato - Rahman, Mufti Fauzi; Yulianita, Neni (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The use of social media as a platform for health education is increasingly growing, including in Indonesia. This study analyzes the communication style of the Instagram account @apoteker_rahmato, managed by Pharmacist Rahmato or called “Mat”, using Roland Barthes' semiotics approach and the Communicator Style Measure (CSM) theory by Robert W. Norton. Barthes' semiotics method is employed to uncover the denotative and connotative meanings of signs in educational video content, while the CSM theory analyzes 10 characteristics of the applied communication style. The results show that Pharmacist Rahmato combines the Impression Leaving, Friendly, and Precise communication styles, enriched with Dramatic, Relaxed, and Animated Expressive elements. This approach enables the delivery of accurate, structured, and easily understood health information while building an emotional connection with the audience through a friendly and casual style. His warm and professional delivery successfully integrates health education into light yet meaningful everyday conversations, especially for the younger generation on social media. This study asserts that a combination of formal and casual elements in health communication can enhance the effectiveness of message delivery and eliminate rigidity in medical information